Pengaruh Terapi Bermain Pada Anak Usia Prasekolah Terhadap Kehilangan Kontrol Dalam Hospitalisasi Di Ruang Anak Rsud Ngudi Waluyo Wlingi - Erna Susilowati; Rita Mei Dwi V (coba, 2015)
At child in age pre school at first times taken care in hospital, they experienced hospitalization stress. They experience lost control (ancient) and trouble in interaction with environment (nurse, friend and next door patient). The feeling can arouse from to face something new and have never experienced it before, feel balmy and not save. Playing activities as usual have to be Limited, routinely they done daily at home, they can not conduct it at hospital. They way to minimize hospitalization stress with arrangement of environment and perform activity like game. Hence researcher perform a research concerning “Influence of Play Therapy at child in Age of Preschool to Lost Control in Hospitalization “. This research target was to know the influence of play therapy at child in age of pre used school to lost control in hospitalization in child room of RSUD Ngudi Waluyo Wlingi Blitar. Research design pre experiment the types was pre post test design. Its population was all children in age of pre school that experiencing taken care in hospital in child room of RSUD Ngudi Waluyo Wlingi Blitar (25 children age of pre school). Sample taken counted 24 respondents. Use purposive sampling. Appliance and data collecting used observation with checklist. Data analyzed including editing, coding, scoring, tabulating. Research result with 24 respondents, reaction of lost control in hospitalization before giving of play therapy got value 3-4 (62,5%) counted is children in bad category. Value 5-7 (37,5%) counted 9 children with enough category. Reaction of lost control in hospitalization after giving play therapy got value 8-10 (100%) in good category. From research result can be concluded that change of reaction of control at child in age pre school in hospitalization before and after play therapy in child room RSUD Ngudi Waluyo Wlingi Blitar give influence to lost control in hospitalization so that child become co- operative to the therapy treatment of healing. Key word : Play therapy, lost control (hospitalization process),Child in age of pre school